Oral Malodor-A Menace To Periodontist - Vishwas, Anjum; Shiromany, Aseem (Bangladesh Journal of Medical Science, 2012)
Oral malodor significantly affects our daily social life. It affects a large population and is a psychological setback to those suffering from it. This common disease has been really ignored for too long by periodontists, even though the most common cause is related to subgingival microbiota and coating of the tongue. It has been proved that a link exists between oral malodor and periodontal disease. Similar processes exist for the development of oral malodor and the progression of periodontitis. Compounds associated with oral malodor like volatile sulfur compounds (VSCs) are mainly produced by the gram negative, anaerobic bacteria associated with periodontitis. These VSC may further contribute to the etiology and pathogenesis of periodontal disease, so the purpose of this review article was to correlate the relationship between oral malodor and adult periodontitis. DOI: http://dx.doi.org/10.3329/bjms.v11i2.9355 Bangladesh Journal of Medical Science Vol. 11 No. 02 April 2012: 74-79